2022
DOI: 10.1093/mnras/stac810
|View full text |Cite
|
Sign up to set email alerts
|

The PEPSI exoplanet transit survey (PETS) I: investigating the presence of a silicate atmosphere on the super-earth 55 Cnc e

Abstract: The study of exoplanets and especially their atmospheres can reveal key insights on their evolution by identifying specific atmospheric species. For such atmospheric investigations, high-resolution transmission spectroscopy has shown great success, especially for Jupiter-type planets. Towards the atmospheric characterization of smaller planets, the super-Earth exoplanet 55 Cnc e is one of the most promising terrestrial exoplanets studied to date. Here, we present a high-resolution spectroscopic transit observa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Unlike D16b, our excellent transit depth agreement with Morris et al (2021) and Meier Valdés et al (2022) tentatively excludes a cloud-free hydrogen-dominated atmosphere (see details in Appendix D). This is consistent with unsuccessful searches for atoms and molecules in transit (Ehrenreich et al 2012;Ridden-Harper et al 2016;Esteves et al 2017;Tabernero et al 2020;Zhang et al 2021b;Keles et al 2022). While Tsiaras et al (2016) reported a hint of HCN based on Hubble observations, no molecules-including HCN-were detected in ground-based high-dispersion spectroscopy (Deibert et al 2021).…”
Section: Interpretation Of Resultssupporting
confidence: 63%
“…Unlike D16b, our excellent transit depth agreement with Morris et al (2021) and Meier Valdés et al (2022) tentatively excludes a cloud-free hydrogen-dominated atmosphere (see details in Appendix D). This is consistent with unsuccessful searches for atoms and molecules in transit (Ehrenreich et al 2012;Ridden-Harper et al 2016;Esteves et al 2017;Tabernero et al 2020;Zhang et al 2021b;Keles et al 2022). While Tsiaras et al (2016) reported a hint of HCN based on Hubble observations, no molecules-including HCN-were detected in ground-based high-dispersion spectroscopy (Deibert et al 2021).…”
Section: Interpretation Of Resultssupporting
confidence: 63%
“…The raw and detrended photometric time-series data are available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsweb.u-strasbg.fr/ cgi-bin/qcat?J/A+A/ Winn et al 2011;Demory et al 2011;Bourrier et al 2018), and an orbital period of only 17.7 hr, 55 Cnc e is larger than most USP planets. 55 Cnc e's bulk density favours the presence of an atmosphere (Dorn et al 2017;Crida et al 2018;Bourrier et al 2018), possibly SiO- (Schaefer & Fegley 2009) or N-dominated (Miguel 2019), but so far no observations have provided definitive evidence for such an atmosphere (Ehrenreich et al 2012;Ridden-Harper et al 2016;Tsiaras et al 2016;Esteves et al 2017;Jindal et al 2020;Tabernero et al 2020;Deibert et al 2021;Zhang et al 2021;Keles et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The PEPSI-LBT Exoplanet Transit Survey (PETS) is a large (∼400 hour) survey of transiting exoplanets using the PEPSI high-resolution spectrograph on the Large Binocular Telescope (LBT). The first paper resulting from the survey set limits on the atmospheric presence of atomic species that could be vaporized from the crust of the super-Earth 55 Cnc e (Keles et al 2022). In this second paper in the series, we analyze our emission and transmission spectra of KELT-20 b.…”
Section: Introductionmentioning
confidence: 99%